2015
DOI: 10.1093/nar/gkv1224
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific replacement of the thymine methyl group by fluorine in thrombin binding aptamer significantly improves structural stability and anticoagulant activity

Abstract: Here we report investigations, based on circular dichroism, nuclear magnetic resonance spectroscopy, molecular modelling, differential scanning calorimetry and prothrombin time assay, on analogues of the thrombin binding aptamer (TBA) in which individual thymidines were replaced by 5-fluoro-2′-deoxyuridine residues. The whole of the data clearly indicate that all derivatives are able to fold in a G-quadruplex structure very similar to the ‘chair-like’ conformation typical of the TBA. However, only ODNs TBA-F4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(83 citation statements)
references
References 46 publications
(60 reference statements)
7
76
0
Order By: Relevance
“…On the contrary 8-Br-dG double substitutions in the TBA produced a decrease in the affinity of the TBA variants for thrombin. From these experiments we can conclude that one single modification of guanine by 8-BrdG is allowed for thrombin recognition but double modification is detrimental for thrombin binding and it confirms that thrombin binding is not dependent of the thermal stability of TBA variants as shown by other authors [17,19]. …”
Section: Thrombin Binding Affinitysupporting
confidence: 82%
See 1 more Smart Citation
“…On the contrary 8-Br-dG double substitutions in the TBA produced a decrease in the affinity of the TBA variants for thrombin. From these experiments we can conclude that one single modification of guanine by 8-BrdG is allowed for thrombin recognition but double modification is detrimental for thrombin binding and it confirms that thrombin binding is not dependent of the thermal stability of TBA variants as shown by other authors [17,19]. …”
Section: Thrombin Binding Affinitysupporting
confidence: 82%
“…Although there is no clear relationship between the structure and the biophysical properties in the antiproliferative behavior [16] recent research has taken this direction [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, G 8 and T 9 in the T 7 G 8 T 9 loop stack on the G-quartet at the 5′-end whereas T 4 and T 13 , in the T 12 T 13 and T 3 T 4 loops, stack on the G-quartet at the 3′-end. Structural studies, performed by means of both X-ray and NMR techniques, showed that T 4 , G 8 , T 9 , and T 13 have an important role in stabilizing the TBA-Q [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, the whole set of our results constitutes a solid basis of chemical and physical knowledge about (i) the Q-folding capacity of the two sequences T30695 and TBA in comparison with those of the corresponding (4-dimethylamino)azobenzene conjugated ones, about (ii) the structural behavior of the unmodified Qs and their variants in solution with different solvents and, finally, on (iii) their photoresponsive properties. This information may be useful in any future biological and biotechnological application envisaged for these two aptamers, taking into account that both T30695 and TBA have an important biological activity, since T30695 binds to and inhibits the HIV-1 integrase at nanomolar concentrations [ 24 , 29 , 30 ], whereas TBA [ 27 , 28 , 31 , 32 , 33 , 34 ] binds to and inhibits the thrombin, causing an anticoagulant effect.…”
Section: Introductionmentioning
confidence: 99%
“…was able to improve the functionality of TBA. In the first study, they introduced 5′‐fluoro‐2′‐deoxyuridine residues to positions T4 and T13, achieving remarkable improvements in melting temperatures and anticoagulant activity . In the second study, they added an extra residue at the 3′‐end or at both ends of the original TBA sequence, linked through 3′–3′ or 5′–5′ phosphodiester bonds, resulting in strong improvements in the thermal stability of TBA …”
Section: Introductionmentioning
confidence: 99%